Schreiben an den Grenzen der Sprache : Studien zu Améry, Kertész, Semprún, Schalamow, Herta Müller und Aub. - Siguan, Marisa (Linguae & litterae., 2014)
This book examines works on the experiences of dictatorship and concentration camps in 20th century history to investigate the question of how terror, violence, and pain can be transformed into literature. What narrative tools do these texts use to communicate liminal experiences at the outer limits of what can be said, how do they deal with the tension between fact and fiction, and what potentials dwell within this literature of remembrance?